Pengaruh Labelisasi Halal Terhadap Keputusan Pembelian Melalui Minat Beli Produk Kosmetik Wardah Pada Pengguna Tiktok - Rohmah, Afifah Nur; Bianda, Ryan; Munir, M. Misbakul (Universitas Labuhanbatu, 2024)
This study aims to determine whether the influence of halal labeling has a positive and significant effect on purchasing decisions through buying interest in wardah cosmetic products on Tiktok. This study uses descriptive quantitative research, the population in this study are wardah cosmetic users who are also tiktok users. The sampling technique used non-probabilty sampling with a sample size of 200 respondents. The results of this study indicate that labeling has a proven positive and significant effect on purchasing decisions, buying interest has a positive and significant effect on purchasing decisions, and halal labeling can directly influence purchasing decisions so that the results of this test indicate a positive and significant amount of influence of halal labeling on purchasing decisions through buying interest.